Assessing the neurotoxicity of the carbamate methomyl in Caenorhabditis elegans with a multi-level approach. (15th March 2021) - Queirós, L.; Martins, A.C.; Krum, B.N.; Ke, T.; Aschner, M.; Pereira, J.L.; Gonçalves, F.J.M.; Milne, G.L.; Pereira, P.
Graphical abstract: Highlights: Methomyl caused behavioral and biometric effects in Caenorhabditis elegans . Post-exposure period allowed the worms to reverse from paralysis. Concentration-dependent recover in the biometric changes was recorded. Acetylcholine increased, but it was not followed by damage in cholinergic neurons. Abstract: The neurotoxicity and developmental effects of a widely applied insecticide (methomyl) was investigated by a multi-level approach (behavior and biometry, biochemical alterations and neurodegeneration) in Caenorhabditis elegans upon a short-term exposure (1 h) and a post-exposure period (48 h). The 1-h exposure to sub-lethal concentrations of methomyl (lower than 0.320 g L −1 ; i.e. below the estimated LC10 ) triggered significant changes on motor behavior and development impairment. The type of movement was significantly altered in methomyl-exposed worms, as well as biometric parameters (worms frequently idle and moving more backwards than controls; small body area, length and wavelength). These effects were followed by an increase of acetylcholine levels. Interestingly, after the 48-h recovery period, movement of previously exposed worms was similar to controls, and a concentration-dependent reversion of biometric endpoints was recorded, pointing out the transient action of the carbamate in line with an apparent absence of cholinergic neurons damage. This study provided new insight on the neurotoxicity of methomyl by showing that effects on movement and development were transient, and apparently did not result in neurodegeneration in cholinergic neurons. Moreover, these findings reinforced the advantages of using C. elegans in a multi-level approach for pesticide effects assessment.